Immigration schools in the city of Santiago: Elements for an education against racism (Polis (Santiago), 2018)
Public schools in segregated neighbourhoods of Santiago have been emptied of Chilean students that parents relocate in other schools, but with the arrival of immigrant children, schools manage to continue operating. They are schools located in the city center, in sectors that account for the abandon of the state and the agony of paved streets and noble mansions, now converted into budget accommodation for immigrants. In this scenario, children of immigration become secondary players, but because of the crisis are finally protagonists of the survival of the educational institution. Useful children allow continuity of schools while they are mistreated by their origin. The purpose of this article is to describe everyday racism experienced by Peruvian immigrant children based on the speech that adults of the educational community that welcomes them display. How are they characterize, how are they evaluated? Is foreignness inherited from their parents, the border that prevents their integration?
Keywords: peruvian immigration; peruvian immigrant children; racism; foreignness; border